Household Coping and Recovery Strategies from Nature’s Wrath: Rising from the Ruins of in the Aftermath of Haiyan - Ravago, Majah-Leah V (Archīum Ateneo, 2023)
The purpose of our study is to shed light on the households’ welfare in the aftermath of a disaster. A few months after a disaster is critical since the overall welfare of the people is at its lowest. Our objective is to assess households’ coping and recovery strategies in the aftermath of a disaster brought about by typhoons. We take the case of Typhoon Haiyan and its affected households six months after the incident to distil lessons for both the affected community and the country as a whole. The case of typhoon Haiyan is interesting given its unprecedented strength and intensity. Haiyan was one of the strongest storms ever recorded with wind speeds of more than 315 kilometres per hour (km/h). It triggered a storm surge that reached over four meters; rapidly swallowing the coastal towns of Eastern and Western Samar and Leyte provinces. This resulted in severe loss of lives and enormous damage to both public and private infrastructure. Utilizing the Philippine Center for Economic and Development (PCED) Social Protection (SP) Survey; we investigate the various risk management and coping mechanisms that the Haiyan-affected families employed six months after the fateful incident. We examine if these strategies aided their recovery. We find that 36% of the household in the sample still have not yet experienced even partial recovery; six months after the disaster. We also find that the most prominent coping activities are taking precautionary measures and asset disposal. Precautionary measures include savings; asset accumulation; and various instruments of (mostly informal) insurance that can be drawn upon to cope with the disaster. However; when disaggregated as to who undertakes precautionary measures; the poor segment of the population lags; which increases their vulnerability. Although government assistance positively aided in the recovery of the poor. For non-poor households; the financial loss due to typhoon Haiyan is tremendous such that government assistance is not enough to improve their immediate recovery.